2011
DOI: 10.1128/jcm.00127-11
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Invasive Infection with Fungemia Due to Microascus cirrosus after Heart and Lung Transplantation in a Patient with Cystic Fibrosis

Abstract: Scopulariopsis species are rarely but increasingly recognized as opportunistic pathogens in immunocompromised patients. We report on a patient suffering from cystic fibrosis who developed disseminated fungal infection due to a rare Scopulariopsis species, Microascus cirrosus, after heart and lung transplantation. Despite antifungal combination therapy with voriconazole and caspofungin, the patient died 4 weeks after transplantation. Diagnostic difficulties and optimal management of disseminated Scopulariopsis/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
63
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 29 publications
(21 reference statements)
2
63
0
2
Order By: Relevance
“…In agreement with earlier reviews of clinical cases (17,22), S. brevicaulis was the most commonly isolated species in our study. S. gracilis was the second most commonly isolated species in our study, which is interesting since this fungus has never been reported in human infections or isolated from clinical specimens.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with earlier reviews of clinical cases (17,22), S. brevicaulis was the most commonly isolated species in our study. S. gracilis was the second most commonly isolated species in our study, which is interesting since this fungus has never been reported in human infections or isolated from clinical specimens.…”
Section: Discussionsupporting
confidence: 93%
“…However, a thorough taxonomic molecular study is still lacking. Scopulariopsis isolates from clinical cases were identified mostly by performing a BLAST search in GenBank (17,21,22). Our study demonstrated that this approach is not very useful, mainly due to the lack of reference sequences for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations